Impact of anabolic steroids on male fertility and the role of post-cycle therapy in recovery - Dorobek, Wioleta; Szerej, Krzysztof; Walczak, Dawid; Stankiewicz, Katarzyna; Świeczkowski-Feiz, Janusz (Journal of Education, Health and Sport, 2024)
Introduction: AAS are a group of hormones that greatly influence the strength and size of muscle. They are widely used by athletes and bodybuilders. Yet research indicates that the use of these compounds has significant implications for male reproductive health as well. The aim of the study: This study was intended to analyze systematically the relationship between AAS use and men’s reproductive health; looking at both what influence AAS has on semen quality and male hormone levels and how post-cycle treatment (PCT) might help in the restoration of any adverse effects caused by AS. Methods: This review was based on available data collected in the PubMed database and Google Scholar web search engine using anabolic-androgenic steroids, male fertility, hypogonadism, post-cycle therapy, and reproductive health. Results: Results suggest that AAS use can lead to testicular atrophy, while research shows that anabolic steroid abuse impairs normal sperm production. These findings include aspermia, oligospermia, or aspermatogenesis. The time period for recovery of sperm quality is also different after use of anabolic steroids, and all cases are expected to have a profound impact on spermatogenesis over the long term. Anabolic steroids may suppress the HPG axis and decrease the male’s fertility hormone, testosterone. If PCT is combined with hCG or SERMs, a person’s own regular hormone levels return after 10 weeks with good prospects for recovery from low testosterone. Conclusion: Studies show that the use of AAS seriously affects the male reproductive system and may even have long-term consequences for this function. PCT seems to offer a reasonable method for re-establishing the hormonal equilibrium and hence proving fertile offspring, which reinforces the need for careful AAS use and monitoring. Further research will be needed before any moves can be taken towards optimizing PCT regimes, in addition to the as-yet-determined long-term consequences for male fertility.